An Early Case of Complete Androgen Insensitivity Syndrome - Leen Matalka MD; S. Joy Dean MD; Giovanna Beauchamp MD; Bhuvana Sunil MD (SAGE Publishing, 2023)
Inguinal hernias are rare in female infants, and when present, there is an increased incidence of androgen insensitivity in these infants. We present a case of bilateral inguinal hernias in a 26-day-old full-term phenotypic female. On physical exam, the patient was found to have bilateral palpable inguinal masses which were suspected to be testicular tissue on ultrasound. Patient also had bilateral inguinal hernias, but otherwise there were no other concerning symptoms, and the remaining physical examination was overall unremarkable. Initial workup included a pelvic ultrasound that did not visualize a uterus or ovaries. In addition, genetic testing confirmed normal male genotype with 100% 46, on fluorescence in situ hybridization (FISH) and array comparative genomic hybridization (CGH) was negative and did not reveal any copy number changes. Molecular testing was consistent with a diagnosis of androgen insensitivity syndrome with hemizygous pathogenic variant in the androgen receptor (AR) gene (deletion of Exon 2 of AR gene Xq12 ). This case highlights the importance of a high clinical suspicion of complete androgen insensitivity syndrome (CAIS) in a phenotypic female infant with inguinal hernias. To our knowledge, this is one of the earliest diagnoses of CAIS in a phenotypically female infant.